Rhetoric and Anti-Racism in Social Work: A Study in the Philosophy of Language - Lesser, Danielle (Cranfield University, 1993)
This thesis is concerned with the nature of understanding in multi-racial social work practice (MRP), and in particular with the philosophy of anti-racist social work. After a review of the past and present literature on MRP which charts the development of anti-racism and black perspectives in social work, it is concluded that new approaches are needed to take account of the importance of racism conceived as a linguistic resource. A consideration of the wider literature on race and racism leads on to an exploration of hermeneutic philosophy as a general guide to the analysis of problems of communication and understanding in social work. The work of Gadamer and Derrida is reviewed in some detail, in the context of wider developments in the philosophy of language and in literary criticism and textual analysis. It is argued that analysis of social work texts can offer new insights into the problems of formulating guidelines for anti-racist practice. Two exemplary analyses are presented: the first of Dominelli 's text Anti-Racist Social Work and the second of Ahmad's Black Perspectives in Social Work. Finally, it 1S suggested that this analysis demonstrates the utility, and complementarity, of Gadamerian and Derridean perspectives in this effort - and that we must recognise that the positions we adopt on the best way forward are necessarily provisional, just as the commonly understood meanings of key terms in the debate about race and social work remain provisional.